One goal, different strategies: An analysis of national broadband plans in Latin America - Galperin, Hernan (2013)
Purpose: The ambitious government initiatives currently underway to accelerate broadband development indicate a major shift from the consensus that prevailed during the 1990 s in the telecommunications sector. To what extent does this change represent a return to the period before market liberalization and the privatization of government‐run telecom services? What are the main objectives of national broadband plans and which policy tools are best suited to achieve them? This paper aims to analyze these questions through a comparative analysis of the goals, policy instruments and network‐deployment models of the most relevant national broadband plans adopted in Latin America. Design/methodology/approach: The paper takes the form of a comparative analysis of the goals, policy instruments and network‐deployment models of the most relevant national broadband plans adopted in Latin America. Findings: Common patterns and key differences between the initiatives adopted in five countries (Argentina, Brazil, Chile, Colombia and Mexico) are identified and compared to those deployed in developed countries. Variations in the strategies adopted are linked to national differences in economic endowments and the broader processes of political change in Latin America. Originality/value: To the best of the authors' knowledge, this is the first paper making this comparative analysis.